Effects of the earthworm Eisenia andrei on methanogens in a cattle-impacted soil: A microcosm study - Koubová, Anna (Jihočeská univerzita, 2016)
The potential of earthworms Eisenia andrei to regulate functional microbiota in cattle-impacted soil was investigated in the laboratory microcosm experiment. Methanogenic archaea and anaerobes were characterised using phylogenetic microarray and phospholipid fatty acid analysis, respectively.
Effects of the earthworm Eisenia andrei on methanogens in a cattle-impacted soil: A microcosm study
Keywords: Cattle winter pasture; methane emission; Methanosarcina sp.; microarray AnaeroChip; PLFA; real-time PCR.; Cattle winter pasture; methane emission; Methanosarcina sp.; microarray AnaeroChip; PLFA; real-time PCR.